Autumn Warming Delays the Downregulation of Photosynthesis and Does Not Increase the Risk of Freezing Damage in Interior and Coastal Douglas-fir - Noordermeer, Devin; Velasco, Vera Marjorie Elauria; Ensminger, Ingo (Frontiers in Forests and Global Change, 2021)
During autumn, evergreen conifers utilize the decrease in daylength and temperature as environmental signals to trigger cold acclimation, a process which involves downregulation of photosynthesis, upregulation of photoprotection, and development of cold hardiness. Global warming will delay the occurrence of autumn low temperatures while daylength remains unaffected. The impact of autumn warming on cold acclimation and the length of the carbon uptake period of species with ranges that encompass diverse climates, such as Douglas-fir (Pseudotsuga menziesii), remains unclear. Our study investigated intraspecific variation in the effects of autumn warming on photosynthetic activity, photosynthetic pigments, and freezing tolerance in two interior (var. glauca) and two coastal (var. menziesii) Douglas-fir provenances. Following growth under simulated summer conditions with long days (16 h photoperiod) and summer temperatures (22 °C/13 °C day/night), Douglas-fir seedlings were acclimated to simulated autumn conditions with short days (8 h photoperiod) and either low temperatures (cool autumn; 4 °C/-4 °C day/night) or elevated temperatures (warm autumn; 19 °C/11 °C day/night). Exposure to low temperatures in the cool autumn treatment induced downregulation of photosynthetic carbon assimilation and photosystem II efficiency, increased the size and de-epoxidation of the xanthophyll cycle pigment pool, and caused development of sustained nonphotochemical quenching. Seedlings in the warm autumn treatment exhibited no downregulation of photosynthesis, no change in xanthophyll cycle pigment de-epoxidation, and no development of sustained nonphotochemical quenching. Albeit these changes, freezing tolerance was not impaired under warm autumn conditions compared to cool autumn conditions. Interior Douglas-fir seedlings developed greater freezing tolerance than coastal seedlings. Our findings suggest that autumn warming, i.e., short photoperiod alone, does not induce downregulation of photosynthesis in Douglas-fir. Although autumn warming delays the downregulation of photosynthesis, the prolonged period of photosynthetic activity does not bear a trade-off of impaired freezing tolerance.